Irish stereotype in American cinema : stories of violence - Szczypa, Piotr (Studia imagologica, 2021)
"Discussing the role of violence in the Irish stereotype, this book is a fascinating story of the changing perception of the Irish in America as told by American cinema. From Levi and Cohen, Irish Comedians (1903) to The Irishman (2019), some of the productions analyzed here are timeless classics; others have almost been forgotten. What they have in common is the presence of violence as the key ingredient in the construction of Irish characters. In his insightful study, Piotr Szczypa employs imagological perspective to investigate the evolution of their portrayal in American films, showing not only how the Irish have adjusted to America but also how America has embraced Irishness"--